Effects of broadcasting supplemental feed into roadside vegetation on home range and survival of female northern bobwhite - Byron R. Buckley; Alicia K. Andes; Blake A. Grisham; C. Brad Dabbert (Wildlife Society Bulletin)
ABSTRACT Declines in northern bobwhite (Colinus virginianus) populations have led landowners in Texas, USA, to develop various management strategies to combat waning abundance. One common management strategy is to provide supplemental feed to bobwhites, despite the paucity of information regarding the effects of supplemental feed on bobwhite space use and survival. We examined survival and home range of bobwhites using the technique of spreading supplemental feed into roadside vegetation in the Texas Rolling Plains. The study sites were divided into 8 (404.6‐ha) units randomly designated as treatment (feed provided) or control (feed withheld). Treatment and control units were rotated during the second field season to minimize potential habitat bias. Treatment units received approximately 69.1 kg/km of milo (Sorghum bicolor) twice per month. We captured and radiomarked 197 female bobwhites (82 treatment [48: 2010–2011; 34: 2011–2012], 115 control [64: 2010–2011; 51: 2011–2012]) from autumn 2010 to spring 2012. Females were monitored for location and survival with radiotelemetry 3–4 times/week. Average home‐range size was similar on control and treatment units (47.6 ha [8.7 SE] and 46.2 ha [10.3 SE], respectively). We estimated survival rate with the nest survival model in Program MARK. We observed an increase in survival rate on treatment units compared with control units, regardless of year or environmental conditions. Our results suggest that distributing supplemental feed into roadside vegetation positively influences bobwhite survival with no reduction in home range size. © 2015 The Wildlife Society.